ALLEVIATING STRESS OF SCLERTIUM ROLFSII ON GROWTH OF CHICKPEA VAR. BHAKKAR-2011 BY TRICHODERMA HARZIANUM AND T. VIRIDE - A. Javaid; A. Ali; A. Shoaib; I. H. Khan (Journal of Animal and Plant Sciences, 2021)
Chickpea (Cicer arietinum L.) is attacked by Sclerotium rolfsii at the seedling stage and the resulting collar rot disease significantly reduces the survival percentage of the seedlings and ultimately yield of the crop. In order to reduce environmental pollution caused by the use of synthetic fungicides, this study was carried out to use two biocontrol agents, namely Trichoderma harzianum and T. viride, against S. rolfsii, and to investigate their effect on plant growth, yield and physiology of chickpea var. Bhakkar-2011. S. rolfsii inoculation reduced dry weight of shoot, root and grains by 21.4%, 36.5% and 49%, respectively, over negative control. T. harzianum and T. viride increased shoot dry weight by 120% and 362%, root dry weight by 132% and 138%, and grain yield by 1109% and 572%, respectively, over positive control (S. rolfsii inoculated only). The effects of the pathogen and the two biocontrol agents were also studied on chlorophyll, carotenoid and phenolic contents as well as on activities of antioxidant enzymes viz. peroxidase (POX), phenylalanine ammonia lyase (PAL) and catalase (CAT). S. rolfsii inoculation suppressed chlorophyll and carotenoid contents while both the Trichoderma spp. increased these parameters many folds. Phenolic content and activities of POX, PAL and CAT were generally increased due to S. rolfsii but became normal due to application of Trichoderma spp. This study concludes that T. harzianum and T. viride are the potential biocontrol agents for control of collar rot of chickpea var. Bhakkar-2011.
Keywords: Biocontrol; chickpea; Sclerotium rolfsii; Trichoderma harzianum; Trichoderma viride